Development of a procedure for isolation, identification and quality assessment of bovine spermatids and evaluation of their fertilizing ability in vitro - Pasquariello, Rolando; Di Filippo, Francesca; Bonumallu, Sai Kamal Nag; Fagali Franchi, Fernanda; Pistucci, Ramona; Franciosi, Federica; Lodde, Valentina; Iannuzzi, Alessandra; Luciano, Alberto Maria; Brevini, Tiziana A. L.; Gandolfi, Fulvio (Frontiers in Bioengineering and Biotechnology, 2025)
Intracytoplasmic spermatid injection into oocytes has limited efficiency in cattle, with no offspring generated so far, partly due to ambiguous spermatid identification. This study aimed to develop and validate a method for isolating and characterizing bovine spermatids to improve the efficiency of spermatid intracytoplasmic injection. First, we optimized a protocol for spermatid isolation from bull testis using a discontinuous Percoll gradient and 10 μm mesh cell strainers. Next, we established a stage-specific separation strategy based on DNA content, size, and granularity using flow cytometry to distinguish round and elongating/elongated spermatids suitable for molecular analysis. Morphological assessment confirmed that 72.5% of isolated cells were at the spermatid stage, supported by a high haploidy rate, spermatid-specific transcript expression (PRM1, PRM2, SPACA9, SPERT), and SPERT protein detection. Viability assays showed that spermatids maintained intact DNA at 0 and 24 h at 4°C and 37°C, though mitochondrial activity and ROS levels increased over time, suggesting oxidative stress. When spermatids were injected into oocytes (n = 82), only 13.4% formed two pronuclei, whereas 46.3% exhibited a single pronucleus and a condensed chromatin spot, indicating incomplete activation or fertilization failure. This work contributes to refining bovine intracytoplasmic injection protocols. Future applications of this approach, particularly if functional spermatids can be derived from spermatogonia or embryonic cells, could help shorten the generational interval in cattle breeding.